Case Report: A Paternal 20q13.2-q13.32 Deletion Patient With Growth Retardation Improved by Growth Hormone - Liu, Yu; Yang, Ying; Chu, Liming; Ren, Shuai; Li, Ying; Gao, Aimin; Wen, Jing; Deng, Wanling; Lu, Yan; Kong, Lingyin; Liang, Bo; Shao, Xiaoshan (Frontiers in Genetics, 2022)
Interstitial chromosome 20q deletions, containing GNAS imprinted locus, are rarely reported in the past. Hereby, we presented a Chinese boy with a novel 4.36 Mb deletion at paternal 20q13.2-13.32, showing feeding difficulty, malnutrition, short stature, lower limb asymmetry, sightly abnormal facial appearance and mild intellectual abnormality. With 3 years’ growth hormone treatment, his height was increased from 90 cm to 113.5 cm. This report is the first time to describe the outcome of clinical treatment on a patient with this rare chromosomal 20 long arm interstitial deletion, containing GNAS locus, which may facilitate the diagnosis and treatment of this type of patient in the future.